A LITERARY STUDY ON NIDANAPANCHAKA OF PANDU ROGA - Kaushik, *Priyanka; Khobragade, Namrata (International Journal of Ayurveda and Pharma Research, 2018)
Pandu means pallor. In this disease there is predominance of paleness all over the body. due to its similarity it can be co-related with modern disease anaemia. Pandu Roga is explained by almost all of our Acharyas. This article is based on Nidanapanchaka of Pandu Roga from Ayurvedic texts as Charak samhita, Susruta samhita, Astanga hrudaya etc with all commentaries. Rasavaha and Raktavaha srotas are chiefly involved in pathogenesis of Pandu Roga. The changing lifestyle of human being by means of Ahara and Vihar plays a major role in manifestation of various diseases. Pandu Roga is also one of them. Our faulty dietary habits and lifestyle produces Ama which further causes Agnimandya and ultimately Amayukta Ahararasa produced. It hampers Rasa Dhatu utpatti and manifests Pandu Roga. Aggravated Pitta is responsible for the production of Posaka (nutrient portion) from the Rasadhatu as a result depletion of Rakta takes place. The detail knowledge of Nidanapanchaka and types of Pandu Roga will help in its diagnosis and management in this modern era also.